Communicative Characteristics in Communication Patterns between Students and Lecturers at the Faculty of Tarbiyah and Teacher Training through WhatsApp Social Media - Yulistari, Novita; Wisnarni, Wisnarni (Fakultas Ushuluddin, Adab dan Dakwah IAIN Kerinci, 2023)
This study aims to identify the communicative character in the communication patterns between students and lecturers through WhatsApp social media, analyze the supporting factors, and reveal the inhibiting factors. This is qualitative field research employing a descriptive approach to understand the observed communication phenomena. Data were collected through observation, interviews, and documentation, with participants consisting of students and lecturers at IAIN Kerinci. The findings indicate that communicative character plays a crucial role in building effective communication patterns between students and lecturers via WhatsApp. Key elements of communicative character include politeness, proper use of language, openness, message clarity, accuracy, consistency in replying, and mutual respect for time. Supporting factors comprise the ability to convey information, availability of time, awareness to maintain communication ethics, and mutual respect for opinions. Inhibiting factors involve differences in communication styles, unclear communication objectives, lack of response, time constraints, and limited communication skills. These findings highlight the need to strengthen digital communication ethics in academic environments, particularly in utilizing social media as an effective medium for learning interaction.